2001
DOI: 10.1212/wnl.57.11.2089
|View full text |Cite
|
Sign up to set email alerts
|

[ 123 I]β-CIT SPECT imaging assessment of the rate of Parkinson’s disease progression

Abstract: - The rate of dopaminergic loss in PD is significantly greater than that of healthy controls, and [123I]beta-CIT SPECT imaging provides a quantitative biomarker for the progressive nigrostriatal dopaminergic degeneration in PD. As new protective and restorative therapies for PD are developed, dopamine transporter imaging offers the potential to provide an objective endpoint for these therapeutic trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
214
3
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 331 publications
(236 citation statements)
references
References 38 publications
18
214
3
1
Order By: Relevance
“…7 Previous studies have shown a linear reduction of striatal DaT binding in early PD, with estimated annual rates of decline ranging from 4% to 10%. [8][9][10][11][12] In our study, assuming a constant decline, the estimated absolute annual rate of decline of striatal DaT binding was around 5%. It is important to highlight that we could not calculate the relative rate of decline compared to age-expected normal values at the time of the first scan, since we did not have those data.…”
Section: Discussionmentioning
confidence: 46%
“…7 Previous studies have shown a linear reduction of striatal DaT binding in early PD, with estimated annual rates of decline ranging from 4% to 10%. [8][9][10][11][12] In our study, assuming a constant decline, the estimated absolute annual rate of decline of striatal DaT binding was around 5%. It is important to highlight that we could not calculate the relative rate of decline compared to age-expected normal values at the time of the first scan, since we did not have those data.…”
Section: Discussionmentioning
confidence: 46%
“…DAT-SPECT has been proven to be an objective tool for monitoring PD progression. (Marek et al, 2001;Tatsch et al, 1997;Weng et al, 2004;Winogrodzka et al, 2001Winogrodzka et al, , 2003. [ 123 I]-β-CIT SPECT have been used in a group of 50 early-stage PD patients showing an average decrease of 8% in the whole striatum (8% in the putamen and 4% in the caudate) at 12-month follow-up (Winogrodzka et al, 2003).…”
Section: Dopaminergic Systemmentioning
confidence: 99%
“…[ 123 I]-β-CIT SPECT have been used in a group of 50 early-stage PD patients showing an average decrease of 8% in the whole striatum (8% in the putamen and 4% in the caudate) at 12-month follow-up (Winogrodzka et al, 2003). Sequential SPECT scans using [ 123 I]-β-CIT demonstrated a decline in striatal uptake of 11.2% per year in PD patients, compared with 0.8% per year in controls (Marek et al, 2001).…”
Section: Dopaminergic Systemmentioning
confidence: 99%
“…Biochemical BMs used in clinical practice and clinical trials include measuring CSF oligoclonal bands to confirm the diagnosis of MS, 10 -12 and functional imaging of dopaminergic neurons in PD with dopamine transporter ligands, measures of dopamine metabolism (fluorodopa), or others. 13,14 Anatomical BMs include magnetic resonance imaging (MRI) of lesion burden or cerebral atrophy in MS 10,15-17 and confirmation of the clinical diagnosis of stroke with computed tomography (CT) or MRI. 18 In fact, in the absence of clinical signs or symptoms, these imaging methods can be used in isolation to diagnose stroke (silent stroke).…”
Section: Biomarkersmentioning
confidence: 99%
“…BMs have, however, been used extensively in clinical trials aimed at altering the progression of disease. 4,13,[41][42][43][44] Specifically, imaging measures of dopaminergic nigrostriatal integrity have been used to examine potential neuroprotective effects of drugs. In some of these studies, the BMs identified relative preservation of the dopaminergic system in subjects treated with dopamine agonists, 42,43 suggesting slowing of disease progression.…”
Section: Assessments Of Disease Severity Progression and Responses mentioning
confidence: 99%